Evaluation of Road Performance and Need for Crossing Facilities in the PT Nikomas Gemilang Area - Budiman, Arief; Intari, Dwi Esti; Suzanti, Wiwien; Faishal, Achmad (Jurnal Fondasi, 2025)
PT Nikomas Gemilang area is a highly active zone. Besides being an industrial area with heavy traffic, the location has market activities with many pedestrians crossing the road, causing traffic disruptions. This research discusses the performance of a road in providing service to the traffic flow occurring on the road, analyzes the problems that hinder traffic on a section of the road, and seeks solutions to the traffic hindrances. This research aims to determine the level of service (LOS) of the road and the type of pedestrian crossing facility needs. The research uses the PKJI 2023 reference standards and the Bina Marga Guidelines of the Minister of Public Works Regulation (Permen PU) No: 02/SE/M/2018. The results of this study obtained the performance of the segment on Jalan Raya Serang, in front of the PT Nikomas Gemilang area, Kibin District, where the saturation degree on Side A was 0,70, and on Side B was 0,69 with a level of service (LOS) of C. Therefore, a future road performance estimation was conducted. The road performance feasibility for the next 2 years (2026) was obtained with an estimated saturation degree on both sides of the road of 0,82 (approaching critical). Then, the need for a type of crossing facility on Jalan Raya Serang was determined with a road type of 4/2-TT and a P value of 596 people/hour, V value of 9554 vehicles/hour, and a PV2 value of 5,44×1010, leading to the conclusion that the type of crossing facility needed is a pelican cross.